2021
DOI: 10.1111/epi.16843
|View full text |Cite
|
Sign up to set email alerts
|

Twenty‐four‐hour patterns in electrodermal activity recordings of patients with and without epileptic seizures

Abstract: Objective Daytime and nighttime patterns affect the dynamic modulation of brain and body functions and influence the autonomic nervous system response to seizures. Therefore, we aimed to evaluate 24‐hour patterns of electrodermal activity (EDA) in patients with and without seizures. Methods We included pediatric patients with (a) seizures (SZ), including focal impaired awareness seizures (FIAS) or generalized tonic‐clonic seizures (GTCS), (b) no seizures and normal electroencephalography (NEEG), or (c) no seiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 35 publications
4
40
0
Order By: Relevance
“…We also subtracted the ictal EDA from a baseline to avoid overestimating ictal EDA. Yet, we cannot completely rule out the EDA contaminants related to stress [33], circadian fluctuation [25], or sleep storms [31] that may lead to higher surges. In our study, patients wore the wristband on either wrist or ankle left or right side.…”
Section: Challengesmentioning
confidence: 98%
See 2 more Smart Citations
“…We also subtracted the ictal EDA from a baseline to avoid overestimating ictal EDA. Yet, we cannot completely rule out the EDA contaminants related to stress [33], circadian fluctuation [25], or sleep storms [31] that may lead to higher surges. In our study, patients wore the wristband on either wrist or ankle left or right side.…”
Section: Challengesmentioning
confidence: 98%
“…EDA can be measured contin-uously outside the hospital setting, using non-invasive and less stigmatizing wearable devices, such as wristbands, making them well-tolerated and accepted by users [20,40,41]. EDA monitoring provides helpful information on GTCS-related sympathetic changes relevant to SUDEP risk assessment and has shown utility seizure detection and prediction, especially when combined with other physiologic modalities [25,[42][43][44][45]. EDA monitoring may be a supplementary and necessary tool for evaluating seizure and SUDEP risk circumstances, particularly when other methods are not available.…”
Section: Assessment Of Sudep Risk and The Role Of Eda Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Billeci et al found that heart rate variability could be used to predict seizures up to 15 min before onset with >80% sensitivity, albeit with a relatively high average false positive rate of 0.41 per hour (almost 10 per day) (128). Signals that show some well-defined ictal changes, such as EDA (129)(130)(131), heart rate, or EMG (121), also show predictive changes prior to seizure onset (32). For instance, a recent study found predictive value in wearable sensor recordings EDA, blood volume pulse, accelerometry, and skin temperature (102).…”
Section: Factors Contributing To Seizure Likelihoodmentioning
confidence: 99%
“…Finally, a clear-cut surge in EDA is observed at onset of GTCS (67)(68)(69), while imbalance in this autonomic biomarker can also be observed in the pre-ictal state (70). A combination of signals can be used for seizure monitoring in the real-world setting, yet the pitfall of this approach is that signal quality, and thus reliability of the approach, is influenced by daily activities and FIGURE 1 | (A,B) A wrist worn commercially available seizure detector with integrated ACC and EDA sensor, (B) displays three electrodes for EDA measure that are in contact with the skin.…”
Section: Sensorsmentioning
confidence: 92%